Medical rehabilitation: a study of problems of legal definition. The intersection of the concepts of medical rehabilitation, prevention and treatment - E. V. Gameeva; A. A. Kostin; G. S. Alekseeva; E. U. Ogneva; P. G. Gabay; L. V. Pashigorova; E. V. Kalita (Исследования и практика в медицине, 2020)
Purpose of the study. To analyze the legal issues, related to the definition of «medical rehabilitation» established in Russian legislation. Materials and methods. A comparative review of the definitions "medical rehabilitation" formulated by World Health Organization and the Russian legislator is made. The main problems of the legal definition of "medical rehabilitation" are studied, including: the problem of distinguishing between "medical rehabilitation" and "treatment". Results. The definition of the term "medical rehabilitation" and terminology used for medical rehabilitation are not consistent in Russian law (legislation still includes such archaic definitions as "rehabilitation treatment" and "rehabilitation medicine"). There is also no unified approach to the question of whether medical rehabilitation is a part of treatment or whether it is an independent stage of medical care. The boundaries between the concepts of "medical rehabilitation" and "treatment" are blurred. Conclusion. The absence of clear boundaries between the definitions of “medical rehabilitation” and “treatment” leads to the risk of violation of licensing requirements by medical organizations, because to determine the list of works (services) to be licensed, it is necessary to correctly determine the specifics of the services provided. The correct classification of a service as medical rehabilitation or medical treatment also effects on the specialization of the involved medical specialists, as well as on the allocated structural units of medical organization. The analysis shows that the main difference between treatment and rehabilitation is the approach. The approach to rehabilitation is broader, it’s primary goal is to return the patient to his previous social status, rather than clinical recovery. At the same time, the main difficulty in distinguishing the mentioned above definitions is related to the fact that the method underlying the medical service is actually licensed, but the same tools and methods can be used both in treatment and medical rehabilitation. Due to these ambiguities, it appears that the current legislation needs to be improved.